Kinetic investigation of the ion angular distribution in capacitive radio-frequency plasmas - Shihab, Mohammed; Mussenbrock, Thomas (Physics of plasmas, 2017)
One of the key parameters in the context of plasma assisted processing in semiconductor fabrication using capacitive radio-frequency plasmas is the ion flux distribution at the substrate. Whereas the ion energy distribution function determines the etching rate and selectivity, the ion angular distribution controls the etching profile. In this contribution, we reveal the effect of the ion flux and the sheath potential on the ion angular distribution and the direct ion heat flux at the bottom of etching profiles in geometrically symmetric plasma reactors. The ion angular distribution and the direct ion heat flux are calculated as a function of the sheath potential, the driving frequency, and the phase shift between the two distinct harmonics of the driving voltage of dual frequency discharges. For this task, self-consistent particle-in-cell simulations subject to Monte Carlo collision are carried out. The results from particle-in-cell simulations which are computationally very expensive are compared and verified with those from the novel ensemble-in-spacetime model. It is confirmed that increasing the voltage of the high-frequency component, the high-frequency component, and/or make a phase shift of π/2 between the dual frequency, narrow the ion angular distribution and increase the direct ion heat flux to the etching profile bottom. In all simulation cases, a correlation between the narrowing of the ion angular distribution and the increase of the sheath potential and the sheath ion flux is found.